Positioning blinatumomab in the frontline of adult B-cell acute lymphoblastic leukemia treatment - Pourhassan, Hoda; Agrawal, Vaibhav; Pullarkat, Vinod; Aldoss, Ibrahim (Frontiers in Oncology, 2023)
Blinatumomab is a bispecific T cell engager that has shown efficacy in relapsed/refractory Philadelphia chromosome (Ph)-positive and Ph-negative acute lymphoblastic leukemia (ALL). Considering its favorable safety and activity in advanced ALL, blinatumomab as a targeted immunotherapy is fast gaining a frontline position in the ALL treatment paradigm. There have been multiple completed and ongoing studies showing significant promise with improved response rates and survival outcomes and decreased treatment toxicity and need for multi-agent chemotherapy regimens. The early use of blinatumomab has established success in Ph-negative and Ph-positive B-ALL, and this has extended to older adults with ALL who have historically had substantially inferior outcomes compared to their pediatric and young adult counterparts. Herein we will review the current data describing the early use of blinatumomab in newly diagnosed adults with B-cell ALL and future directions.